2009
DOI: 10.1002/bmc.1346
|View full text |Cite
|
Sign up to set email alerts
|

Automated precolumn derivatization system for analyzing physiological amino acids by liquid chromatography/mass spectrometry

Abstract: An automated method for high-throughput amino acid analysis, using precolumn derivatization high-performance liquid chromatography/electrospray mass spectrometry (HPLC/ESI-MS), was developed and evaluated. The precolumn derivatization step was performed in the reaction port of a home-built auto-sampler system. Amino acids were derivatized with 3-aminopyridyl-N-hydroxysuccinimidyl carbamate, and a 3 microm Wakosil-II 3C8-100HG column (100 x 2.1 mm i.d.) was used for separation. To achieve a 13 min cycle for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 38 publications
0
74
0
Order By: Relevance
“…7 Changes in the aminogram in a disease vs normal state have been observed, reflecting the metabolic modulation of AAs, glucose and lipids; for example, aminogram changes in liver disease. 8, 9 Aminogram changes in obesity and diabetes have been observed, and might reflect the metabolic modulation induced by insulin resistance.…”
mentioning
confidence: 99%
“…7 Changes in the aminogram in a disease vs normal state have been observed, reflecting the metabolic modulation of AAs, glucose and lipids; for example, aminogram changes in liver disease. 8, 9 Aminogram changes in obesity and diabetes have been observed, and might reflect the metabolic modulation induced by insulin resistance.…”
mentioning
confidence: 99%
“…They indicated that carbohydrate ingestion increased insulin secretion which raised plasma tryptophan and lowered the concentration of the competing amino acids such as branched neutral amino acids in rats [18]. Carbohydrate ingestion was shown to decrease plasma free amino acid levels [19], and glucose intake resulted in a decrease in large neutral amino acids such as methionine, phenylalanine, tyrosine, and tryptophan [20]. These results suggested that an increase in plasma levels of glucose or insulin may increase the transport of some amino acids using various transporters, thus decreasing the concentration of such amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…APDS has a more hydrophobic structure compared with THAS, and thus APDS derivatives are suitable for the separation on the reversed phase column. APDS was used for the analysis of amino acids (72,73) and more than 100 compounds having amino group in biological fluid. The transition of all the protonated molecules to the common product ion at m/z 121 was monitored (71).…”
Section: Valproic Acid (Serum) (67)mentioning
confidence: 99%